Salicylic acid: effect on the physiological quality of Cichorium endivia L. seeds - Fontana, Daniele Cristina; Meira, Daniela; Pollon Zanatta, Thais; Werner, Carla Janaina; Brezolin, Patricia; Kulczynski, Stela Maris (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Salicylic acid (SA) is known to be involved in a series of physiological processes in the improvement of seed germination and vigor. The aim of this study was to evaluate the effect of SA concentrations on the physiological quality of escarole (Cichorium endivia L.) seeds, Escarola Lisa® cultivar. Escarole seeds were soaked for 24 h at concentrations 0, 0.05, 0.1, 0.15, and 0.2 mM of a similar to salicylic acid (Bion®) and afterwards submitted to germination and vigor tests (laboratory and greenhouse). The tested seed lots differed in their physiological quality. The use of salicylic acid does not present profits for the physiological quality of escarole seeds. However, it is suggested that new studies be carried out by testing this product under stress conditions or applied in stages after seed germination.